Does Income Diversification Reduce Poverty in Rural Households? - , Nsikak-Abasi A. Etim; , Glory E. Edet (Archives of Current Research International, 2016)
A study was conducted to profile poverty in rural households based on income diversification. The effect of diversification of income sources on poverty was investigated. Multistage sampling procedure was employed to select the representative farming households for the study. Survey data from 150 households were obtained with the aid of questionnaire. Data were analyzed quantitatively using the Foster, Greer, Thorbecke FGT) weighted poverty measure. Results showed the non-diversity of income (sources by most farming households. Result of analysis revealed that poverty was negatively related to income diversification as the incidence of poverty was lower for households with diverse income sources whereas poverty gap and squared-poverty gap were higher for households with single income source. The t-value of only one of the decomposed sub-groups was significant (P<0.1). Providing enabling environment for meaningful agricultural production through the provision of inputs for rural households to embark on multi-agricultural enterprises would be a sensible policy decision.